Augmented reality as biology learning media based-on artificial intelligence technology: a systematic literature review - Muhfahroyin, Muhfahroyin; Santoso, Handoko (JURNAL BIOEDUKATIKA, 2024)
Augmented reality is a technology that connects the virtual and real world with the help of a camera. Augmented reality technology is very important to get an overview of the progress and the real impact of its use in biology learning. Furthermore, through systematic literature review analysis, we searched for biology learning publications that utilized augmented reality. The results of the study show that there are no biology journals on a scopus basis that discuss the use of augmented reality the most. The trend of using augmented reality in biology learning from 2012-2022 started in 2016 and was highest in 2020. Biological material that uses the most augmented reality media is heart and blood flow material. The level of education that makes the most use of augmented reality is college. The types of research which is most widely used are research and development. The obstacles that occur are the lack of facilities and the lack of teacher training in utilizing augmented reality. All levels of education can take advantage of augmented reality with teacher skills facilitating student learning. All levels of education can take advantage of augmented reality with teacher skills facilitating student learning